1991
DOI: 10.1099/00221287-137-1-187
|View full text |Cite
|
Sign up to set email alerts
|

Root surface colonization of non-cereal crop plants by pleomorphic Azospirillum brasilense Cd

Abstract: Root surface colonization by Azospirillum brasilense Cd of tomato, pepper and cotton plants under normal growth conditions and soybean plants under normal and water-stress conditions was monitored by scanning electron microscopy and bacterial counts. A. brasilense Cd was capable of efficiently colonizing the elongation and root-hair zones of all four plant species tested. In these zones, the bacteria mainly colonized the root surface (tomato, soybean), root-hairs (pepper), or both (cotton), by single cells (to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 36 publications
2
52
0
1
Order By: Relevance
“…Other studies on root colonization by Azospirillum have revealed the presence of fibrillar material that anchors the bacterial cells to the root surface and establishes connections between cells within bacterial aggregates [3,4,30]. In these images, bacteria are closely packed but clearly embedded in an amorphous material that is presumably composed of exopolysaccharides of bacterial origin.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other studies on root colonization by Azospirillum have revealed the presence of fibrillar material that anchors the bacterial cells to the root surface and establishes connections between cells within bacterial aggregates [3,4,30]. In these images, bacteria are closely packed but clearly embedded in an amorphous material that is presumably composed of exopolysaccharides of bacterial origin.…”
Section: Discussionmentioning
confidence: 95%
“…8a-f) show that all of the Azospirillum strains examined can colonize leaves forming aggregates, a prominent feature of the colonization of leaf surfaces [4,7,30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To achieve ideal biocontrol efficacy, the antagonists must colonize the rhizosphere soil and sustainedly occupy favorable ecological sites in the environment. Previous studies have illustrated that the long-term colonization of antagonists is correlated to soil moisture (or the water content of soil), temperature, soil aeration, pH, soil salinity, as well as the continuous supply of nutrients (Sessitsch et al, 2004;Bashan et al, 1991;Bevivino et al, 2005;Cavaglieri et al, 2005;de-Bashan and Bashan, 2008).…”
Section: Obstacles To the Long-term Colonization Of Antagonists: The mentioning
confidence: 99%
“…The increase in K nutrient uptake might be due to the synergistic effect of higher N uptake (Srinivasan Rao et al, 1997). The preferential potassium accumulation in the leaves as a result of bacterial inoculation might be also related to changes in membrane activity and subsequently proton efflux in roots (Bashan et al, 1991).…”
Section: Phosphorous Uptakementioning
confidence: 99%